The foundations of jurisprudence : an introduction to Imāmī Shīʿī legal theory - al-Ḥillī, al-ʿAllāmah. (The Classical Shīʿah Library, 2016)
Foundations of Jurisprudence: An Introduction to Imāmī Shīʿī Legal Theory is a critical edition of the Arabic text with a parallel English translation of Mabādiʾ al-wuṣūl ilā ʿilm al-uṣūl by al-ʿAllāmah al-Ḥillī, introduced, edited and translated by Sayyid Amjad H. Shah Naqavi. Al-ʿAllāmah al-Ḥillī participated in the leading debates of his day and applied his vast erudition in philosophy, logic, and theology to the paramount subject of jurisprudence. This text presents an exemplar of the rich revival of Shīʿī scholarship in the thirteenth and fourteenth centuries of the Common Era. Concise, yet comprehensive, this work sets the standard for the subsequent development and discussion of Imāmī Shīʿī legal theory, such that its influence can be traced through to modern times. This dual-text edition is indispensable for students and scholars of Imāmi Shīʿī jurisprudence.